Faire réussir des "bacs pro" en IUT - Sonia Lefeuvre; Laurent Cosnefroy; Michel Le Nir; Thierry Michalot; Jean-Yves Seguy (Les éditions de la Maison des sciences de l'Homme, 2023)
This article reports on a singular experiment: the one carried out at the Institut Supérieur Professionnel (ISP) to welcome only vocational baccalaureate students in the first year of the Institut Universitaire de Technologie (IUT) so that, at the end of this year, they join the second year IUT students. Compared to the national success rates of vocational baccalaureate students in the IUT, the success of ISP students is greater. Furthermore, from our quantitative survey conducted at this IUT, we were also able to observe that their involvement, commitment to work and sense of belonging to the institution were higher than those of students with a general or technological baccalaureate enrolled at the same IUT. To try to understand the factors that might explain these results, we made observations within the recruitment committees and interviews with the teaching staff.